Determination of thermophysical properties of cupuassu (Theobroma grandiflorum) dry almonds - Elisa Santana Cunha; Geovana Pires Araújo Lima; Jorge Henrique Oliveira Sales; Elizama Aguiar de Oliveira (The Journal of Engineering and Exact Sciences)
In comparison to cocoa, little has been reported on the drying of cupuassu almonds that can be used to produce cupulate, a chocolate type product. Thus, in this study thermophysical properties of cupuassu dry almonds (moisture = 9.68 % d.b.) were determined as: thermal conductivity (k) of 0.14 kW/(m.K), specific heat (cp) of 2.86 kJ/(kg.K), thermal diffusivity (?) of 4.8·10-5 m²/s, effective diffusivity (Deff) of 9.94·10-10 - 6.29·10-10 m²/s and activation energy (Ea) of 14.90 kJ/mol. These results showed a similarity of values between cupuassu and cocoa and allows to perform more specific studies for the development of dryers for the cupuassu almonds.